Tafsir Virtual - Amir, Abdul Muiz; Syamsuddin, Sahiron (SUHUF, 2021)
Religiousity in social media has influenced the quality of interpretation toward the editorial of the revelation, particularly in the content of Da’wa or preaching in the pocalyptic genre being popularized by Indonesian preachers via YouTube. This study aims at investigating the relationship between the practice of interpreting the Qur’an and Hadith and the impact of the distribution of apocalyptic narrative content on religious extremism on YouTube. That study is achieved by the observation using a critical analysis design which incorporates intertextuality and deconstruction approaches. This study found the practice of reducing the interpretation toward the editorial revelation in the content of da’wah in apocalyptic time. This study also demonstrated the existence of a symbiotic relationship among the practice of reducing interpretations through the use of non-authoritative sources. This type of behavior may have an impact on the spread of religious extremism narratives on YouTube. Both of those can be used by transnational jihadist extremist groups to recruit new members in Indonesia